2014
DOI: 10.1177/2047487314538857
|View full text |Cite
|
Sign up to set email alerts
|

Secondary medical prevention and clinical outcome in coronary artery disease patients with a history of non-coronary vascular intervention: A report from the CORONOR investigators

Abstract: In modern practice and real life conditions, the higher risk of CAD patients with a history of non-coronary vascular intervention is taken into account, with more intense secondary prevention and similar risk factor control than patients without such history. In spite of the level of secondary prevention, patients with a history of non-coronary vascular intervention remain at high risk of cardiovascular events. This should be an incentive to discuss more stringent objectives for secondary prevention in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…21,22 Thus, in relation to previous studies, our study mainly focused on all-cause death and drew a conclusion for this "hard endpoint" in MI patients. Comparing our results to the studies where the study populations was stable post-MI patients, CORONO study conducted by Delsart P et al showed that the rate of all-cause death for their stable CAD patients without coronary vascular intervention history was around 5.5% at 1 year, 23 which was higher than the corresponding rate in our 18-month DAPT group (3.7%) and similar to the rate in our 12-month DAPT group (5.9%). The baseline rate of DAPT use for their non-coronary vascular intervention patients was 20%, and angiotensin system antagonists, beta-blockers and statins were widely prescribed in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…21,22 Thus, in relation to previous studies, our study mainly focused on all-cause death and drew a conclusion for this "hard endpoint" in MI patients. Comparing our results to the studies where the study populations was stable post-MI patients, CORONO study conducted by Delsart P et al showed that the rate of all-cause death for their stable CAD patients without coronary vascular intervention history was around 5.5% at 1 year, 23 which was higher than the corresponding rate in our 18-month DAPT group (3.7%) and similar to the rate in our 12-month DAPT group (5.9%). The baseline rate of DAPT use for their non-coronary vascular intervention patients was 20%, and angiotensin system antagonists, beta-blockers and statins were widely prescribed in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, it is today well recognized that CAD patients who present markers of diffuse atherosclerosis are at higher risk as compared with patients with focal disease [4][5][6][7][8][9][10][11][12][13][14][15][16]32,35,36]. As a perfect illustration of this, patients with high-SYNTAX score have shown to experience poor outcome after PCI [24][25][26][27].…”
Section: Long Lesion/stent As a Marker Of Diffuse Atherosclerosis And Hmentioning
confidence: 99%
“…10,11 Segundo diretrizes internacionais de prevenção secundária das DCV, recomenda-se tratamento medicamentoso ao longo da vida com antiagregantes plaquetários, betabloqueadores, estatinas e inibidores da enzima conversora de angiotensina (IECA). [11][12][13][14] Com o aumento do uso desse tratamento para prevenção secundária, a cada 10.000 pacientes, mais de 104 vidas poderiam ser salvas e 191 eventos isquêmicos recorrentes poderiam ser evitados se a maioria desses pacientes com doenças crônicas fossem tratados na Atenção Primária. A dinâmica proposta pela Estratégia Saúde da Família (ESF), centrada na promoção da qualidade de vida e intervenção dos fatores que a colocam em risco, permite a identificação mais acurada e um melhor acompanhamento dos indivíduos com vistas à prevenção de doenças, principalmente as cardiovasculares, tendo um impacto sobre as taxas de incidência das mesmas.…”
Section: Introductionunclassified